'Live Together in Peace on the Way to God.' The Rule of Augustine as a 'Rule of Peace' - Walraet, Pierre-Paul (Editorial Uniagustiniana, 2019)
Love, harmony, unity, and peace are key to Augustine's ideal of the religious life. Augustine's Praeceptum is explored from the perspective of peace. The monastic precepts, admonitions and recommendations elaborated in the Praeceptum are geared toward peace in the community and finally toward eternal peace (in Deum, in pace). To this end, the Praeceptum emphasizes harmonious living together in community, observing the community of goods, fostering mutual respect in common and personal prayer, avoiding cases of anger and dealing with them, fraternal correction through a restorative process, love that is not self-seeking but serves the common good, religious obedience to the superior. The brothers are called to seek peace and pursue it, aware that the peace here on Earth is still imperfect. The Praeceptum reflects aspects of Augustine's vision and teaching on peace elaborated in Book XIX of the De Civitate Dei. In his Ennarationes in Psalmos the bishop of Hippo uses images of a harbor, a furnace and a cartwheel to illustrate challenges in achieving peace, and points out faulty expectations for peaceful life in a religious community. Authentic peace lived in community strengthens the longing and love for the spiritual beauty of God who is Perfect Peace